2016
DOI: 10.1016/j.wear.2016.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of wear of diamond wire on surface morphology, roughness and subsurface damage of silicon wafers

Abstract: Wear of fixed abrasive diamond wire affects the quality of sliced silicon wafers, necessitating replacement of the costly wire. This paper analyzes the effect of wire wear on the surface morphology, roughness, and subsurface damage of as-cut single crystal silicon wafers. Scanning electron microscopy, confocal microscopy, and focused ion beam machining (FIB) are used to evaluate the surface morphology, areal surface roughness, and subsurface damage (cracks). Results show that, with increased wire wear, the waf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…Recent industry trends indicate a shift from loose abrasive slurry (LAS) to fixed abrasive diamond wire sawing (DWS) . The slicing action in LAS consists of a three‐body abrasion mechanism in contrast to two‐body abrasion in DWS, which cuts silicon by a combination of ductile cutting and brittle fracture . Consequently, scribing can be used to understand the fundamentals of DWS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent industry trends indicate a shift from loose abrasive slurry (LAS) to fixed abrasive diamond wire sawing (DWS) . The slicing action in LAS consists of a three‐body abrasion mechanism in contrast to two‐body abrasion in DWS, which cuts silicon by a combination of ductile cutting and brittle fracture . Consequently, scribing can be used to understand the fundamentals of DWS.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have reported the ductile cutting of silicon . The ductile behavior of silicon is attributed to stress‐induced phase transformation caused by the large compressive stresses generated in front of the scriber . Ductile removal of silicon during DWS could produce less micro‐cracks, thereby enhancing the fracture strength of the wafer.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, diamond wire sawing technique on multicrystalline silicon wafer grew up at a very high speed due to costeffectiveness compared to traditional slurry sawing process [1,2]. It was demonstrated that diamond wire sawing (DWS) has several superiorities over multiwire slurry sawing (MWSS), that is, higher slicing speed, less saw damage layer, better environmental friendship, and potential for cutting thinner wafers [3,4]. However, diamond wire sawing brings a big texturing problem due to the surface with less saw damage layer and less start point for normal acid texturing [5].…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The wafering process involves interaction of abrasive grits with the silicon material. [5][6][7] Depending on the condition of abrasives, the surfaces of these wafers frequently exhibit a mixture of ductile and brittle surface characteristics. [8][9][10][11] The abrasives plastically deform the surface of silicon which are constrained within a surrounding elastic region, thus giving rise to residual stresses.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Depending on the condition of abrasives, the surfaces of these wafers frequently exhibit a mixture of ductile and brittle surface characteristics. [8][9][10][11] The abrasives plastically deform the surface of silicon which are constrained within a surrounding elastic region, thus giving rise to residual stresses. 12 Evaluation of these residual stresses is critical to accurate understanding of the mechanical integrity of these wafers, which may undergo further processing into solar cells and microelectronics.…”
Section: Introductionmentioning
confidence: 99%